Incidence and Molecular Characterization of Rotaviruses of Cattle and Buffalo Calves in Amravati Region, Maharashtra - Ade, M.J.; Ingle, V.C.; Tembhurne, P.A.; Tumlam, U.M.; Kadam, A.S.; Bhojne, G.R.; Sonkusale, P.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Fecal samples of diarrheic and non diarrheic cattle calves (198) and buffalo calves (90) were collected during January 2018 to July 2018. Screening of fecal samples for the presence of rotavirus was carried out by commercially available rapid Rota virus Ag detection kits. A total of 35 out of 288 (12.15%) fecal samples were found positive by latex agglutination test. Highest incidence (20.63%) was found in Yavatmal district followed by Amravati (16.00%), Akola (13.33%), Buldana (6.77%) and lowest (3.57%) in Washim. A higher incidence (14.50%) in cattle was observed as compared to buffalo ( 8.04%) calves of 0 to 6 months of age. Further higher incidence was noted in male and female both in cattle as compared to buffalo calves.
Keywords: Rota Virus; Cattle; Buffalo; Diarrheic; RNA PAGE